Lexical Cohesion Used In Donald Trump’s Campaign Speech - Ni Komang Happy Trindira Windayani (PRAGMATICA : Journal of Linguistics and Literature, 2023)
The title of this research is "Lexical Cohesion Used in Donald Trump's Campaign Speeches". Lexical cohesion is one of the most important tools for bringing text together. Lexical cohesion is grouped into five types. Due to the large number of types, research on lexical cohesion needs to be carried out and the problems to be studied are: the types and uses of the most common types found in Donald Trump's campaign speeches. The theory used is the theory of lexical cohesion types taken from Cohesion in English by Halliday and Hassan (1976). This study uses four of Donald Trump's speeches as data sources. Data collection is carried out in the form of library research, which searches for and downloads data sources and then reads the relevant data included in it. All data is grouped into the appropriate type group. The data that has been collected is analyzed descriptively and frequency. The results of the study show that five types of lexical cohesion are found in Donald Trump's campaign speeches. The five types of lexical cohesion found are repetition, synonym, superordinate, general words, and collocation. The mostly type of lexical cohesion found is repetition.